‘First Do No Harm’: physician discretion, racial disparities and opioid treatment agreements - Beck, Adrienne Sabine (Journal of medical ethics, 2022)
The increasing use of opioid treatment agreements (OTAs) has prompted debate within the medical community about ethical challenges with respect to their implementation. The focus of debate is usually on the efficacy of OTAs at reducing opioid misuse, how OTAs may undermine trust between physicians and patients and the potential coercive nature of requiring patients to sign such agreements as a condition for receiving pain care. An important consideration missing from these conversations is the potential for racial bias in the current way that OTAs are incorporated into clinical practice and in the amount of physician discretion that current opioid guidelines support. While the use of OTAs has become mandatory in some states for certain classes of patients, physicians are still afforded great leeway in how these OTAs are implemented in clinical practice and how their terms should be enforced. This paper uses the guidelines provided for OTA implementation by the states of Indiana and Pennsylvania as case studies in order to argue that giving physicians certain kinds of discretion may exacerbate racial health disparities. This problem cannot simply be addressed by minimising physician discretion in general, but rather by providing mechanisms to hold physicians accountable for how they treat patients on long-term opioid therapy to ensure that such treatment is equitable.